Organized Labor Strikes and Social Spending in Latin America: The Synchronizing Effect of Mass Protest. (May 2020) - Kim, Dongkyu; Kim, Mi-son; Villegas, Cesar
ABSTRACT: The theories and evidence about relationships between democracy and social spending in Latin America are highly contested. A recent study shows that collective protest by organized labor effectively increases social security and welfare spending, whereas mass protest does not have comparable effects on human capital spending in Latin American democracies. This article reexamines the analysis and demonstrates that organized labor alone cannot sway democratic governments. Labor strikes require the synchronizing effect of mass protest to obtain government concessions. Only through concurrent episodes of mass protest can organized labor overcome the numerical disadvantage of pressing democratic government for social welfare spending. In understanding the relationship between labor protests and social welfare spending through the lens of insider-outsider dichotomy, it is critical to consider the synchronizing effect of mass protests. The findings remain robust with alternative measures of democracy and various model specifications.